Toxicidade e estresse oxidativo das células mesenquimais estromais de tecido adiposo de cão em diferentes passagens de cultura - Sprada, Arícia Gomes (2014)
Stem cells are undifferentiated cells capable of autorenovation and differentiation in several cell lines. These cells can be found in various tissues such as bone marrow, skin, nervous tissue, adipose tissue and dental pulp. Adipose tissue is an alternative source of mesenchymal stem cells because it consists in a less invasive collection and provides higher number of cells when compared to bone marrow. In humans, adipose tissue metabolism differs according to the anatomical location. In mice, differences in the cellular composition and differentiation capacity of mesenchymal stem cells derived from adipose tissue (ADSCs) were observed according to the anatomical regions. In order to assist researchers in choosing the site of collection and the best cell passage, this study aimed to compare the viability and quality of multipotent mesenchymal stromal (CMEM) derived from subcutaneous and omentum of a dog through indicator of cytotoxicity and oxidative stress in six different passages of culture. The samples of adipose tissue from the both sites were collected from a dog corpse. Cells were processed and cultured in a humidified atmosphere with 5% CO2 and subsequently stained with Trypan Blue and counted in a Neubauer chamber. To assess cytotoxicity the technique of fragmentation and fluorimetry with picogreen dye was used. Also, oxidative stress assays were performed by using fluorimetric assay 2-70-dichlorofluorescein diacetate technique (DCFH-DA) and measuring the levels of thiobarbituric acid reactive species (TBARS). The results showed greater levels of oxidative stress in the first and last passages of both groups, favoring cytotoxicity and cell death.